Islam: knowledge and civilization - Haque, Munawar; Sulaiman, Kabuye Uthman; Soualhi, Bachir; Ariff, Syamsuddin (IIUM Press, 2009)
This book is an outcome of efforts made to consolidate the main topics covered in the International Islamic University Malaysia (IIUM) university required course entitled, 'Islam, Knowledge and Civilization' (UNGS 2040). It has been written basically to acquaint the undergraduate students, majoring in different disciplines with the meaning, objectives, importance and necessity of learning the theme of knowledge and civilization from the Western Islamic perspectives. It is a fact of history that the Muslims did not merely attain political supremacy and found extensive empires, but they also surpassed at one time, all other nations in the field of knowledge and intellectual endeavour. Muslims, as a whole, have been giving birth to men of learning who have been known for their zest for acquiring knowledge, self-sacrifice for its cause and masterly dissertations of the highest quality on different subjects. This work is just an introduction to the subject. With future revised editions, it is expected that the issues under discussion will be dealt with in greater detail and other issues may also be included to keep the subject matter relevant and useful to contemporary times.